2019
DOI: 10.1186/s12885-018-5211-y
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic outcomes and prognostic factors in unresectable gallbladder cancer treated with gemcitabine plus cisplatin

Abstract: BackgroundGallbladder cancer (GBC) is likely to be diagnosed at progressive stages and shows a very poor prognosis. Combination therapy with gemcitabine and cisplatin (GEMCIS) has been widely used as first-line palliative chemotherapy for advanced GBC. This study was designed to investigate the efficacy of GEMCIS and identify prognostic factors in patients with unresectable GBC.MethodsPatients with GBC who were treated with GEMCIS from January 2008 to June 2017 in a single tertiary hospital were included. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…After removal of duplicates, we browsed the titles and abstracts of the remaining 134 studies, and 107 studies were excluded according to the inclusion and exclusion criteria. Then we assessed full-text review of the remaining 27 studies, another 13 studies were excluded and finally 14 retrospective cohort studies were included for meta-analysis (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Basic characteristics of included studies were listed in Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicates, we browsed the titles and abstracts of the remaining 134 studies, and 107 studies were excluded according to the inclusion and exclusion criteria. Then we assessed full-text review of the remaining 27 studies, another 13 studies were excluded and finally 14 retrospective cohort studies were included for meta-analysis (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Basic characteristics of included studies were listed in Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Eight studies incorporating 1,325 patients investigated prognostic value of PLR in GBC patients ( 11 , 14 18 , 20 , 21 ). No significant heterogeneity between groups was observed (I 2 = 33.4%, P = 0.162), and the pooled HR showed that low PLR group had significant better OS than high PLR group ( Figure 4 , HR = 1.34, 95% CI = 1.14–1.57, P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have explored potential clinical factors associated with outcome to first-line CisGem [135][136][137][138]. Within the identified factors, poor performance status, elevated serum lactate dehydrogenase, elevated neutrophil-to-lymphocyte ratio, low hemoglobin, metastatic disease, increased bilirubin, increased neutrophils, and high baseline tumor markers were associated with poor outcome [136][137][138]. In addition, reduction in CA 19-9 during therapy predicted longer patient survival [135].…”
Section: Predictors Of Response To Palliative Chemotherapymentioning
confidence: 99%
“…Moreover, chemotherapy regimens for both are different. 10,11 For unresectable gallbladder carcinomas, the preferred regimen is Gemcitabine based while Platinum-based regimens are preferred for advanced Ovarian carcinomas. [10][11][12]…”
Section: Discussionmentioning
confidence: 99%